Synthesis of Ring II/III Fragment of Kanamycin: A New Minimum Structural Motif for Aminoglycoside Recognition - Sandra G. Zárate; Agatha Bastida; Andrés G. Santana; Julia Revuelta (MDPI AG, 2019)
A novel protocol has been established to prepare the kanamycin ring II/III fragment, which has been validated as a minimum structural motif for the development of new aminoglycosides on the basis of its bactericidal activity even against resistant strains. Furthermore, its ability to act as a AAC-(6′) and APH-(3′) binder, and as a poor substrate for the ravenous ANT-(4′), makes it an excellent candidate for the design of inhibitors of these aminoglycoside modifying enzymes.